Penerapan Metode Waterfall Dalam Perancangan Sistem Informasi Geografis Pemetaan Populasi Ternak Di Kabupaten Malaka Berbasis Web Menggunakan System Block Diagram (Sbd) - Da Silva, Yoseph Ardi Mariano; Nababan, Darsono; Lestari, Anastasia Kadek Dety; Maneno, Regolinda (Department of Information Technology, Universitas Timor, Indonesia, 2024)
Abstract - This research focuses on implementation waterfall method in designing a web-based geographic information system for mapping livestock populations in Malacca Regency using a block diagram (SBD) system. Malacca Regency has dominating livestock potential,This is based on data sourced from (Animal Husbandry Division, Malacca Regency Agricultural Service, 2022), which records the livestock population in 12 sub-districts in Malacca Regency, including 265 horses and 265 cows.71,095 head, 692 buffaloes, as many goats46,337head, 56,078 pigs, 446,072 chickens and 3,299 ducks The aim of this research isto assist Malacca Regency Animal Husbandry Service officers and the community in searching for the location of all livestock spread across Malacca Regency and knowing the percentage data which makes it easier to obtain information.With this information system, it is hoped to make it easier for the public to find the location and number of livestock in Malacca Regency which can be accessed via the website. This research uses the method Waterfall scontains research information in the process of creating the